Needful things - King, Stephen, 1947- (New York : Signet, 1992)
Leland Gaunt opens a shop called Needful Things where there is something for everyone, but of course there is always a very high price to pay.
Booklist.
Publisher's Weekly.
Wilson's Fiction.
Adult
Keywords: Cities and towns -- Fiction; Murder -- Fiction; Stores, Retail -- Fiction; Cities and towns -- Fiction; Homicide -- Fiction; Horror fiction; Stores -- Fiction; Horror tales